2020
DOI: 10.37398/jsr.2020.640214
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Propagation of Polygonatum verticillatum All. A Threatened Medicinal Herb through Seed Explant

Abstract: To conserve and overcome the limitations of traditional propagation, a need was felt to develop an in vitro propagation protocol for Polygonatum verticillatum (L.) All. by using seeds as explant. The present study was undertaken to evaluate the most suitable concentration of plant growth regulators on callus induction and subsequent rhizome and shoot regeneration. Murashige and Skoog (MS) medium fortified with Kn (8mg/l) in combination with IAA (2mg/l) proved most effective in producing maximum amount of callu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In a similar study on P. odoratum, 85% rooting response was observed at 3.0 mg L -1 IBA supplemented MS medium (Kim et al, 2014). Qadir et al (2020), however, reported maximum root induction in P. verticillatum in 26±0.55 days in MS medium fortified with 2 mg L -1 IBA.…”
Section: Root Induction and Proliferationmentioning
confidence: 80%
See 1 more Smart Citation
“…In a similar study on P. odoratum, 85% rooting response was observed at 3.0 mg L -1 IBA supplemented MS medium (Kim et al, 2014). Qadir et al (2020), however, reported maximum root induction in P. verticillatum in 26±0.55 days in MS medium fortified with 2 mg L -1 IBA.…”
Section: Root Induction and Proliferationmentioning
confidence: 80%
“…MS+TDZ (1.0mg/L) +2,4-D(1.0mg/L) showed effective callogenic effect in P. verticillatum from hypocotyl (70±5.00 %) and leaf explants (45%) of in vitro grown plants of P. verticillatum (Tiwari and Chaturvedi, 2018). Qadir et al (2020) reported that in vitro sprouted seed explants pretreated with 1.0 mg/l GA 3 kept at -20° C for a month, produced 60% callus response on Kn (8.0 mg/l) and IAA (2.0 mg/l) fortified MS medium in 33±0.57 days (Park et al, (2018), showed efficiency of 2,4-D at 0.5 mg•L -1 for 87% production of callus in P. stenophyllum Maxim. In the present study, however, leaf explant from in vivo raised plants showed effective callusing (58%) in minimum number of days (20.33 ± 2.3) in MS medium supplemented with TDZ and 2,4-D.…”
Section: Callus Induction From Leaf Explantmentioning
confidence: 99%
“…The present finding is in contradiction with the earlier report in this plant, where NAA (0.5 mg/l) in half strength MS medium was most effective in producing maximum number of roots (4.79 ± 0.69) with maximum root length (1.00 ± 0.30 cm) (Bisht et al 2012). In another study on P. verticillatum, 1.93 ± 0.34 cm long roots regenerated from shoots when inoculated on MS medium supplemented with 2.0 mg/l IBA within 26 ± 0.55 days (Qadir et al 2020). Compared to these two studies, in the present study, more number of roots with higher average root length is formed in significantly lesser number of days.…”
mentioning
confidence: 95%